2001
DOI: 10.1017/s0021932001001213
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in Condom Use in the Context of Hiv/Aids in Zimbabwe

Abstract: Against the backdrop of a high prevalence of the human immunodeficiency virus infection in Zimbabwe, this paper analyses data from the 1997 Zimbabwe Sexual Behaviour and Condom Use Survey to throw light on the degree to which sexually active adults consistently use condoms in high-risk sexual situations. The multivariate results indicate that at the time of the survey, consistent condom use in non-marital relationships is significantly higher for males than females, higher among those who had access to informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 0 publications
1
43
0
Order By: Relevance
“…[23][24][25][26] Our evidence is more nuanced. In longer-term relationships, rightly or wrongly, concerns about disease prevention disappeared but the need to avoid pregnancy typically remained strong.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Our evidence is more nuanced. In longer-term relationships, rightly or wrongly, concerns about disease prevention disappeared but the need to avoid pregnancy typically remained strong.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale survey research and multivariate analyses with populations aged 15-49 years using national and regional surveys from 14 countries in southern, eastern, western and middle Africa [9][10][11][12][13][14][15][16][17][18] uniformly support the conclusion that men, and those who are younger, have higher education, greater economic resources and are urban dwellers are more likely to be condom users. Smaller scale studies in Angola, 19 Kenya, 20,21 Zimbabwe, 22 Rwanda 23 and Cameroon 24 restricted to adolescent populations (15-19 years) obtain the same results with the exception that reported condom use increases with age.…”
Section: Sociodemographic Characteristics Of Condom Usersmentioning
confidence: 98%
“…Condoms are most often reported as used by those who have multiple partners, and in what are variously described as casual, one-time or occasional partnerships rather than repeated, relationship-based or marital sexual partnerships. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][52][53][54][55][56] In fact, Adetunji 110 found marital status to be the strongest predictor of condom use in his analysis of DHS data from Zimbabwe. The greater likelihood of condom use among those with multiple partners and in 'casual' relationships has been found across diverse forms of sexual partnering -among youth with no 'long-term' relationship in Ghana and South Africa, [52][53][54][55][56]111 among those who are married and have additional casual or multiple partnerships in studies in all regions of SSA, 79,82,[112][113][114] and among sex workers in South Africa 33,36 who have both regular and casual sexual partnerships.…”
Section: Noncommercial Relationshipsmentioning
confidence: 99%
“…Some researchers have reported that young people were more likely to use condoms at latest sex in casual than in steady partnerships 23 [. A study in Zimbabwe found that, among males, the likelihood of condom use at last sex with a casual partner was nearly the same as that with a steady partner 24 . Further research may investigate the role of use of other contraceptive methods on condom use.…”
Section: Discussionmentioning
confidence: 99%
“…Correct and consistent use of condoms is the best way to prevent both pregnancy and disease 6 . In Uganda, prevalence of condom use at first sex among unmarried young people aged [15][16][17][18][19][20][21][22][23][24] has been reported to be 37% for females and 59% for males; while use at latest sex among the same age group is 54% for both males and females 7 . The prevalence of HIV in the general population has been 6.4% 7 but has risen 8 .…”
Section: Introductionmentioning
confidence: 99%